Pseudocapacitive Hausmannite Nanoparticles with (101) Facets: Synthesis, Characterization, and Charge‐Transfer Mechanism. Issue 10 (3rd May 2013) - Yeager, Matthew P.; Du, Wenxin; Wang, Qi; Deskins, N. Aaron; Sullivan, Matthew; Bishop, Brendan; Su, Dong; Xu, Wenqian; Senanayake, Sanjaya D.; Si, Rui; Hanson, Jonathan; Teng, Xiaowei
Abstract Hausmannite Mn3O4 octahedral nanoparticles of 18.3±7.0 nm with (101) facets have been prepared by an oxygen‐mediated growth. The electrochemical properties of the Mn3O4 particles as pseudocapacitive cathode materials were characterized both in half‐cells and in button‐cells. The Mn3O4 nanoparticles exhibited a high mass‐specific capacitance of 261 F g−1, which was calculated from cyclic voltammetry analyses, and a capacitive retention of 78 % after 10 000 galvanostatic charge–discharge cycles. The charge‐transfer mechanisms of the Mn3O4 nanoparticles were further studied by using synchrotron‐based in situ X‐ray absorption near edge spectroscopy and XRD. Both measurements showed concurrently that throughout the potential window of 0–1.2 V (vs. Ag/AgCl), a stable spinel structure of Mn3O4 remained, and a reversible electrochemical conversion between tetrahedral [MnIIO4] and octahedral [MnIIIO6] units accounted for the redox activity. Density functional theory calculations further corroborated this mechanism by confirming the enhanced redox stability afforded by the abundant and exposed (101) facets of Mn3O4 octahedra.